A prospective for the role of two-pore channels in breast cancer cells - Hengrui Liu (Global Journal of Cancer Therapy - Peertechz Publications, 2020)
Breast cancer is one of the most common cancers and the second most frequent cause of cancer death among women worldwide. Recently, potential links between cancer and the calcium mobilizing messenger Nicotinic Acid Adenine Dinucleotide Phosphate (NAADP) and its intracellular target Two-Pore Channels (TPCs) have been identified. However, their role in breast cancer cells has not been extensively evaluated, and the understanding of underlying pathways is still lacking. Here we proposed a hypothesis that TPC function is crucial for the cell biology and tumorigenesis of the breast cancer cell. Further study can be done in this field, such as screening the expression of TPC1 and TPC2 in different breast cancers, then testing whether altered expression of TPC1 and TPC2 affects breast cancer and breast cancer stem cells.  It is also valuable to search for the potential targets of TPCs and NAADP calcium signaling in breast cancer cells. This mini-review aims to propose potential research methods and experimental design for future study and will contribute to the raising and development of the research in this field.